Combined Efficacy of Instrument-Assisted Soft Tissue Mobilization and Extracorporeal Shockwave Therapy in Myofascial Pain Syndrome Associated with Knee Osteoarthritis: A Case Report - Sanhita Sengupta; Gaijilung Dangmei; Glory Dangmei; Pritam Das; Md Olive Rahaman (The Bioscan, 2026)
Knee osteoarthritis (KOA) is a progressive degenerative condition associated with pain, stiffness, and functional limitations, particularly in older individuals. Myofascial pain syndrome (MPS), characterized by the presence of trigger points (TrPs), significantly contribute to pain and disability in KOA. This case report is the first to report the combined effect of Instrument-Assisted Soft Tissue Mobilization (IASTM) and Extracorporeal Shock Wave Therapy (ESWT) in the treatment of myofascial pain syndrome associated with KOA. The patient was a 52-year old female with knee pain and TrPs around affected hamstrings and quadriceps muscle, reduced muscle strength, and difficulty in performing daily functional activities. The intervention consisted of IASTM and ESWT, administered three times per week for a duration of four weeks. Baseline assessment was taken for pain intensity, muscle strength, high-sensitivity C-reactive protein (hs- CRP), and functional activity. Following the treatment period, the patient showed considerable improvements in pain intensity, muscle strength, and functional performance. These findings suggest that, integration of IASTM and ESWT may be an effective treatment approach for managing myofascial pain syndrome associated with KOA.